2022
DOI: 10.3389/fnins.2021.782947
|View full text |Cite
|
Sign up to set email alerts
|

Morris Water Maze and Contextual Fear Conditioning Tasks to Evaluate Cognitive Functions Associated With Adult Hippocampal Neurogenesis

Abstract: New neurons are continuously generated and functionally integrated into the dentate gyrus (DG) network during the adult lifespan of most mammals. The hippocampus is a crucial structure for spatial learning and memory, and the addition of new neurons into the DG circuitry of rodents seems to be a key element for these processes to occur. The Morris water maze (MWM) and contextual fear conditioning (CFC) are among the most commonly used hippocampus-dependent behavioral tasks to study episodic-like learning and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 150 publications
(344 reference statements)
1
17
0
Order By: Relevance
“…In the present study, TASE and thymol treatments significantly increased the thickness of the granular zone in the dentate gyrus which corresponds with the previous studies (Amaral et al, 2007). In addition, newly generated neurons in the DG of the hippocampus in mice promote spatial learning and memory (Hernández‐Mercado & Zepeda, 2022), which corresponds with our findings in the MWM and passive avoidance tests. DCX is a microtubule‐associated protein expressed as an early marker protein in the immature granule cells harboring migration and dendritic growth (Spampanato et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, TASE and thymol treatments significantly increased the thickness of the granular zone in the dentate gyrus which corresponds with the previous studies (Amaral et al, 2007). In addition, newly generated neurons in the DG of the hippocampus in mice promote spatial learning and memory (Hernández‐Mercado & Zepeda, 2022), which corresponds with our findings in the MWM and passive avoidance tests. DCX is a microtubule‐associated protein expressed as an early marker protein in the immature granule cells harboring migration and dendritic growth (Spampanato et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Scopolamine, is an approved anticholinergic drug, which can initiate AD-like symptoms, including oxidative stress, Aβ deposition, neurodegeneration, and cognitive decline (Bubser et al, 2012). Morris water maze (MWM) and passive avoidance tasks are behavioral analysis experiments commonly used to analyze episodic-like hippocampal synaptic plasticity in rodents (Hernández-Mercado & Zepeda, 2022). Moreover, molecular markers, such as brain-derived neurotrophic factor (BDNF) and glycogen synthase kinase-3 beta (GSK-3β), are abundantly expressed in the mammalian central nervous system and are involved in regulating gene expression, cell growth, and development (Kisoh et al, 2017).…”
mentioning
confidence: 99%
“…In the present study, we used the MWM to evaluate the learning and memory ability. The MWM is widely used to assess hippocampus-dependent spatial learning and memory and is closely related to hippocampal long-term potentiation (LTP) [ 46 48 ]. In the present study, the increased escape latency, less time in target quadrant C, and reduced target crossing times after IE indicated impaired learning and memory, which were consistent with the results of previous studies [ 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Morris water-maze test is primarily used to test the learning and memory abilities of experimental animals ( Hernández-Mercado and Zepeda, 2021 ). In previous studies, it was found that db/db mice had long-term memory impairment ( Ye et al, 2018 ; Ma et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%